SYNTHESIS CHITOSAN-ETHYLENE DIAMINE TETRA CETATE CHELATING RESIN ISOLATED FROM WINDU SHRIMP’S (Penaeus monodon) SHELL WASTE - Marvin Horale; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2015)
A researchon the utilization of shrimp shell waste are abundan tin the province of East Kalimantan as the source of chitosan and synthesis of the derivative chelating chitosan-ethylene diamine tetra acetate (EDTA) resin and the retention of characterization for Cu(II) ions has been carried out. Chitin were obtained from Windu Shrimp’s (Penaeus monodon) shell through three ways, are deproteination, demineralitation and depigmentation. The obtained chitin were deacetylated with sodium hydroxide at temperature 150-160˚C during 1 hour to obtained chitosan, with contain was 64.4%. Synthesis chitosan-EDTA resin can be done by coupling reacts between diazonium ion from diazotation chitosan with EDTA at temperature 1-3˚C during 1 hour, the product of 70% yield was obtained. The Chitosan-EDTA resin was synthesized has characterization by using FT-IR spectroscopic and scanning electron microscope, shows the spesific functional groups of the resin.